Editors’ Welcome - Marshall, James E.; Newell, Patrick; Beare, Paul (Educational (Re)naissance, 2013)
This issue of Educational Renaissance is devoted to documenting the proceedings from the Fall 2012 Joint Conference of The Renaissance Group (TRG) and the Teacher Education Council of State Colleges and Universities (TECSCU) at the Key Bridge Marriott, Arlington, VA, September 30 - October 2, 2012. The conference, entitled “The Proof of Effective Partnerships: Educators Meeting the Challenges and Opportunities Of the 21st Century,” highlighted outstanding examples of innovative partnerships in teacher preparation. Here we present one article and the proceedings from five selected conference presentations, as well as the multimedia slides from five other sessions.